Comparison of surgery and surgery plus corticosteroid therapy in idiopathic granulomatous mastitis, prospective randomized study (Annals of Medical Research, 2021)
Aim: To compare therapeutic effectiveness of surgery alone with surgery plus corticosteroid in patients with granulomatous mastitis.Material and Methods: The study included 30 patients aged 23-60 years. The patients were randomly assigned into two groups by lot. In-group 1, the patients received 375 mg ampicillin-sulbactam (twice daily, p.o.) for a week; than 32 mg prednisolone was started which was gradually tapered (biweekly by 8 mg) over 8 weeks. Surgery was performed 2 weeks after tapering. In-group 2, the patients received 375 mg ampicillin-sulbactam (twice daily, p.o.) for a week and underwent surgery. During 2-years follow-up, all patients were assessed for etiological factors and recurrence.Results: No significant differences was found in demographic characteristics, smoking habits, oral contraceptive use, presenting complaints, physical examination findings, localization and diagnostic tools used between groups. During follow-up, recurrence was seen in one patient (6.7%) in surgery group and in 3 patients (20%) in steroid group but no significant difference was detected between groups (p>0.05). Conclusion: In patients with granulomatous mastitis, systemic steroid therapy is an effective modality in patients unresponsive to antibiotic therapy after ruling out tuberculosis.
Keywords: Granulomatous mastitis; steroid therapy; surgical treatment; recurrence